Explorations on Sound and New Media Art - José Alberto Gomes (Journal of Science and Technology of the Arts)
This special issue of the Journal of Science and Technology of the Arts is inspired by the first >>| Explorations on Sound and New Media Art Conference, held at the Universidade Católica Portuguesa, School of Arts in Porto, Portugal. Like the conference, this issue seeks to celebrate the convergence of sound, new media, and artistic expression by exploring a wide range of innovative practices, theories, and approaches. It aims to foster meaningful discussions that critically examine traditional notions of art while pushing the boundaries of creativity. Following the conference, we invited various authors to develop and submit their research, with the hope that their contributions will shed further light on how we perceive and construct the world through sonic and new media art practices.